2022
DOI: 10.3390/ijerph19148839
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Fatigue Responses of Endurance- and Strength-Trained Athletes during Incremental Cycling Exercise

Abstract: This study explored the development of neuromuscular fatigue responses during progressive cycling exercise. The sample comprised 32 participants aged 22.0 ± 0.54 years who were assigned into three groups: endurance-trained group (END, triathletes, n = 10), strength-trained group (STR, bodybuilders, n = 10) and control group (CG, recreationally active students, n = 12). The incremental cycling exercise was performed using a progressive protocol starting with a 3 min resting measurement and then 50 W workload wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
(58 reference statements)
1
1
0
Order By: Relevance
“…Lower muscle vascular conductance and maximal cardiac output in the upper limb muscles may have contributed to this effect [32]. Consistent with prior fatigue research where the most intense fatigue was observed at the end of exercise [33,34], our participants self-reported an RPE of "very hard" or "exhausted" after upper limb cycling, affirming the successful fatigue induction in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Lower muscle vascular conductance and maximal cardiac output in the upper limb muscles may have contributed to this effect [32]. Consistent with prior fatigue research where the most intense fatigue was observed at the end of exercise [33,34], our participants self-reported an RPE of "very hard" or "exhausted" after upper limb cycling, affirming the successful fatigue induction in this study.…”
Section: Discussionsupporting
confidence: 87%
“…One of the formulas for obtaining an internal load value using the TRIMP method requires the time in each heart rate zone during a given exercise. Edward proposed eTRIMP method which the ITL result is determines by measuring a product of the accumulated training duration in minutes of 5 HR zones by a coefficient related to each zone (50 to 60% of HRmax x 1; 60 to 70% of HRmax x 2; 70 to 80% of HRmax x 3; 80 to 90% of HRmax x 4; and 90-100% of HRmax x 5), a model which has a relationship moderate to large between measures of training load [2]. Including, since eTRIMP does not require an exercise test, it is more easily implementable in large studies [3].…”
Section: Introductionmentioning
confidence: 99%